2021
DOI: 10.2174/1871527320666210804155617
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Sleep Disturbances in Alzheimer’s Disease

Abstract: : Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by sleep, behavioral, memory, and cognitive deteriorations. Sleep disturbance (SD) is a major disease burden in AD which has a reciprocal relationship with AD pathophysiology. It aggravates memory, behavioral, and cognitive complications in AD. Different studies found that melatonin hormone levels reduce even in the pre-clinical stages of AD. Melatonin is the primary sleep-regulating hormone and a potent antioxidant with neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 86 publications
0
13
0
1
Order By: Relevance
“…Tg2576 rats treated with melatonin confirmed that melatonin could augment the clearance of Aβ through the lymphatic system . Furthermore, melatonin agonists (e.g., ramelteon and agomelatine) could improve the sleep quality in the sleep disorders of AD …”
Section: Potential Therapies For Ad Through Sleep Improvementmentioning
confidence: 81%
See 1 more Smart Citation
“…Tg2576 rats treated with melatonin confirmed that melatonin could augment the clearance of Aβ through the lymphatic system . Furthermore, melatonin agonists (e.g., ramelteon and agomelatine) could improve the sleep quality in the sleep disorders of AD …”
Section: Potential Therapies For Ad Through Sleep Improvementmentioning
confidence: 81%
“…The accumulation of tau may regulate the level of orexins . Melatonin may be a modifier in the pathogenesis of AD, and it can improve the sleep–wake cycle and decrease AD development. , It is worth studying the relationship between the LC-NE system and inflammation. Notably, some receptors of these neurotransmitters may be involved in the pathological progress of AD and be worth further investigation.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…The anti-inflammatory effects of vitamin D may be another explanation for vitamin D deficiency that can lead to sleep disorder in the disease. Additionally, the production of melatonin can be regulated by vitamin D ( 13 ), which is the primary sleep-regulating hormone ( 52 ). Several lines of evidence reveal that melatonin can benefit patients with sleep disorders related to various neurological disorders ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that sleep disorders have a bidirectional relationship with the pathophysiology of AD, worsening the behavioral, cognitive, and memory alterations associated with this disease by increasing the β-amyloid load in response to an inflammatory process induced by these sleep disturbances [145]. In relation to this parameter, a field that has gained great interest in recent years focuses on the neuroprotective role of melatonin, as a reduction of this hormone has been observed in the early stages of AD [146]. Melatonin modulates the expression and function of secretase, thereby inhibiting the amyloidogenic processing of APP and Aβ production.…”
Section: Sleep Patternmentioning
confidence: 99%